2009
DOI: 10.1177/0146167209340904
|View full text |Cite
|
Sign up to set email alerts
|

The Metamorphosis of Narcissus: Communal Activation Promotes Relationship Commitment Among Narcissists

Abstract: Three studies tested the hypotheses that the activation of communal mental representations promotes relationship commitment (communal activation hypothesis) and that this effect is stronger among narcissists than among nonnarcissists (Communal Activation × Narcissism hypothesis). Across experimental, longitudinal, and interaction-based research methods, and in participant samples ranging from college students to married couples, results supported the communal activation hypothesis in two of three studies and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 37 publications
0
39
0
2
Order By: Relevance
“…Second, the trifurcated model demonstrated that narcissistic antagonism is meaningfully related to and may underlie certain negative clinical outcomes, suggesting that antagonism represents a promising and relatively underspecified target for clinical intervention. As previous findings have suggested, targeting narcissistic antagonism could involve techniques designed to increase communal focus (Gilbert, 2005;Hofmann, Grossman, & Hinton, 2011), which has been found to reduce some of the deleterious consequences of narcissism (e.g., Finkel, Campbell, Buffardi, Kumashiro, & Rusbult, 2009) and cause short-term decrements to state narcissism (Giacomin & Jordan, 2014). Consistent with this approach, DBT's interpersonal effectiveness component of therapy could be useful for prioritizing goals related to maintaining positive relationships versus other goals (e.g., self-respect, getting what one wants) (Linehan, 2014).…”
Section: Implications For Clinical Interventionmentioning
confidence: 99%
“…Second, the trifurcated model demonstrated that narcissistic antagonism is meaningfully related to and may underlie certain negative clinical outcomes, suggesting that antagonism represents a promising and relatively underspecified target for clinical intervention. As previous findings have suggested, targeting narcissistic antagonism could involve techniques designed to increase communal focus (Gilbert, 2005;Hofmann, Grossman, & Hinton, 2011), which has been found to reduce some of the deleterious consequences of narcissism (e.g., Finkel, Campbell, Buffardi, Kumashiro, & Rusbult, 2009) and cause short-term decrements to state narcissism (Giacomin & Jordan, 2014). Consistent with this approach, DBT's interpersonal effectiveness component of therapy could be useful for prioritizing goals related to maintaining positive relationships versus other goals (e.g., self-respect, getting what one wants) (Linehan, 2014).…”
Section: Implications For Clinical Interventionmentioning
confidence: 99%
“…Komitmen. Skala komitmen (commitment measures) dari Rusbult (Finkel, Campbell, Buffardi, Kumashiro, & Rusbult, 2009;Finkel, Rusbult, Kumashiro, & Hannon, 2002;Rusbult, Martz, & Agnew, 1998), Skala yang terdiri atas 8 aitem didasarkan pada tiga komponen komitmen, yaitu niat untuk bertahan, kepentingan pribadi atau kelekatan psikologis, dan orientasi jangka panjang. Koefisien reliabilitas (α) pada skala komitmen diperoleh sebesar 0,652.…”
Section: Metode Penelitianunclassified
“…For example, Foster, Shrira, and Campbell (2006) showed that the low levels of relationship commitment that characterize narcissistic individuals is linked to overvaluing agentic aspects of relationships (e.g., physical enjoyment) and undervaluing communal aspects (e.g., emotional connections). Nonetheless, some marriage data have revealed that narcissism predicts higher satisfaction and commitment, but only in cases where narcissistic individuals report high self-esteem (Sedikides, Rudich, Gregg, Kumashiro, & Rusbult, 2004) and communal feelings for the partner (Finkel, Campbell, Buffardi, Kumashiro, & Rusbult, 2009). …”
Section: Narcissism and Newlywed Marriage: Partner Characteristics Anmentioning
confidence: 99%